Pengaruh Tingkat Keuntungan, Literasi Keuangan Syariah dan Religiusitas Terhadap Minat Investasi Emas Syariah di Kalangan Generasi Z Kabupaten Jepara - Richa Armelia Rokhmah; Edi Susilo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The objective of this study is to examine the effect of return rate, Islamic financial literacy, and religiosity on the intention to invest in Sharia-compliant gold among Generation Z in Jepara Regency. The novelty of this study lies in integrating Islamic financial literacy and religiosity within the context of Sharia-compliant gold investment among Generation Z in Jepara Regency, which has rarely been examined simultaneously. In addition, this study employs a survey-based quantitative approach focusing on investment intention through digital platforms, thereby offering a new perspective on the investment behavior of a technologically literate and religiously oriented young generation. This study uses a quantitative approach with a survey method to analyze the effect of return rate and knowledge on investment intention. The data used are primary data obtained from Generation Z respondents through questionnaire distribution. The population of this study consists of Generation Z in Jepara Regency who are actively engaged in investment activities. The sampling technique employed is purposive sampling, with a total sample of 95 Generation Z respondents in Jepara Regency. Data were collected using a Likert-scale questionnaire. The analytical technique applied is multiple linear regression analysis using SPSS version 26. The results indicate that the return rate has a positive and significant effect on the intention to invest in Sharia-compliant gold. Islamic financial literacy has a positive and significant effect on the intention to invest in Sharia-compliant gold. Religiosity also has a positive and significant effect on the intention to invest in Sharia-compliant gold.